2017
DOI: 10.1017/xps.2017.22
|View full text |Cite|
|
Sign up to set email alerts
|

Football and Public Opinion: A Partial Replication and Extension

Abstract: Do events irrelevant to politics, such as the weather and sporting events, affect political opinions? A growing experimental literature suggests that such events can matter. However, extant experimental evidence may over-state irrelevant event effects; this could occur if these studies happen to focus on particular scenarios where irrelevant event effects are likely to occur. One way to address this possibility is through replication, which is what we do. Specifically, we replicate an experimental study that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…At least on the CQ issue, respondents were not affected by the celebratory and nationalist mood in the treatment. In a recent study conducted in the USA that found a direct link between victories by one's favorite college sports teams and evaluations of the political incumbents, the results are similar in that only general evaluative attitudes, such as evaluations of the president and the respondents' university, were affected, not evaluations of the economy or the pope (Busby and Druckman 2018). Furthermore, this study directly measured the change in mood and found that to be significant in affecting political attitudes, lending support to the hypothesized mechanism of a mood effect.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…At least on the CQ issue, respondents were not affected by the celebratory and nationalist mood in the treatment. In a recent study conducted in the USA that found a direct link between victories by one's favorite college sports teams and evaluations of the political incumbents, the results are similar in that only general evaluative attitudes, such as evaluations of the president and the respondents' university, were affected, not evaluations of the economy or the pope (Busby and Druckman 2018). Furthermore, this study directly measured the change in mood and found that to be significant in affecting political attitudes, lending support to the hypothesized mechanism of a mood effect.…”
Section: Resultsmentioning
confidence: 81%
“…These empirical patterns suggest that political attitudes and decisions can be "influenced by irrelevant events that have nothing to do with the competence or effectiveness of incumbent government" (Healy et al 2010, p. 12807). Particularly, the impact of sports victories on political outcomes has been found in democracies such as the USA Miller 2013), Germany (Hagen et al 2004), and Spain (Bagues and Esteve-Volart 2016), which was partially replicated in recent studies (Busby et al 2017;Busby and Druckman 2018).…”
Section: Sports and Politics In Chinamentioning
confidence: 86%
“…Other studies are skeptical of these claims (Fowler and Montagnes 2015;Fowler and Hall 2018) or produce mixed results (Busby and Druckman 2018). 8 Finally, some acknowledge these events' influence but interpret them as instances of democratic accountability working effectively .…”
mentioning
confidence: 99%
“…The last sentence of the abstract for “Football and Public Opinion: A Partial Replication and Extension” as published online in the Journal of Experimental Political Science on 8 November, 2017 contained the following error:While the effects clearly can occur, there relevance to politics remains unclear.It should have read as:While the effects clearly can occur, their relevance to politics remains unclear.The author and publisher apologize for this error.…”
mentioning
confidence: 99%
“…The last sentence of the abstract for “Football and Public Opinion: A Partial Replication and Extension” as published online in the Journal of Experimental Political Science on 8 November, 2017 contained the following error:…”
mentioning
confidence: 99%